Educating children with special needs (New York ; Sydney : Prentice Hall, 1998)
This book is divided into three sections: A number of general issues related to the education of students with special needs; The educational provisions that have been developed for students in regular classes who have special education needs and who can have most, if not all, of these needs satisfied; The circumstances that can make it extremely difficult for some students to learn or progress through the education system.
Keywords: Education; Special education; Mainstreaming in education